Induced breeding failure alters movements, migratory phenology, and opportunities for pathogen spread in an urban gull population - Juliet S. Lamb; Thierry Boulinier (Movement Ecology)
Abstract Background Annual-cycle movements of wildlife are driven by a combination of intrinsic and extrinsic factors. In urban systems, management strategies to reduce human-wildlife interactions could also alter wildlife movement and distribution, with potential effects on key ecological processes such as pathogen spread. Methods To better understand how management actions interact with existing spatial dynamics to mediate wildlife movement patterns, we experimentally subjected urban-nesting yellow-legged gulls to induced breeding failure via egg-oiling. We then followed their movements using bird-borne GPS transmitters throughout the treatment season as well as the following annual cycle and compared them to the movements of tracked gulls whose nests were not oiled, while also accounting for individual and temporal factors known to influence movement patterns including sex, body size, and breeding stage. Results Gulls with oiled nests had smaller breeding-season home ranges, spent more time at breeding sites, made fewer foraging trips, and traveled shorter distances than gulls with non-oiled nests during the treatment season but not during the following breeding season. Gulls were partially migratory, with individuals showing a variety of migratory strategies from year-round residency to long-distance migration to inland urban centers. Although egg-oiling delayed the onset of post-breeding migration, individual migration strategies remaining consistent between years regardless of treatment. Antibody titres against three common pathogens varied among pathogens but not by migration distances or individual characteristics. Conclusions Our results show that induced breeding failure via egg-oiling may have unintended short-term consequences including smaller home range areas, altered habitat use, delayed migration, and longer breeding-site residency, suggesting that management actions aimed to reduce breeding success could increase opportunities for human-wildlife conflict and spread of spatially heterogeneous pathogens at local scales. At the landscape scale, the migration patterns and wintering distribution of yellow-legged gulls are unlikely to be affected by egg-oiling. However, long-distance inland migrations of a portion of the population present a novel pathway for pathogen transmission between and among marine habitats and terrestrial human, livestock, and wildlife populations.